Application of 3D Printing in Intracranial Tumours - Ikponmwosa, Morgan; Ogunsemoyin, Ayodele Olugbenga; Moemenan, Onyekachi Okechukwu; Ezeigwe, Obinna; Darko, Yaw Barimah (New Advances in Medicine and Medical Science Vol. 1, 2023)
The pituitary gland is a small bean-shaped gland located at the base of the brain. Pituitary-based tumors are neuroendocrine tumors that affect the pituitary gland. Pituitary gland imaging employs computed tomography and magnetic resonance imaging. 3D reconstruction of data from CT images can be converted into 3D and then printed as a live anatomical model using a 3D printer. This research intends to show that information obtained from CT scan images can be used to produce 3D-printed specific models for patients and clinicians. A segmentation application was used to create patient-specific models for three clinical situations in order to separate the mass from the bone. The procedure involved image acquisition starting with cross-sectional imaging, segmenting the acquired DICOM image into a 3D model, file and model correction for final print, slicing with the choice of 3D printing material and the proper settings, and concluding with the actual print, print accuracy, and cost analysis. It took between 45 and 90 minutes to segment the region of interest, with the majority of that time being spent segmenting the pituitary. Models were printed in sections since the mass and skull were printed separately. The times needed for printing the mass and the skull base were 20–40 minutes and 4–9 hours, respectively. The overall cost of printing a model was less than $50, and print accuracy was less than 1.7mm.